2010
DOI: 10.3168/jds.2009-2508
|View full text |Cite
|
Sign up to set email alerts
|

The effect of injectable butaphosphan and cyanocobalamin on postpartum serum β-hydroxybutyrate, calcium, and phosphorus concentrations in dairy cattle

Abstract: The objective of this study was to determine the effect of an injection of 10% butaphosphan and cyanocobalamin (Catosal, Bayer, Shawnee Mission, KS) on the day of calving and 1 d later on the prevalence of subclinical ketosis in dairy cattle in the early postpartum period. Cows from 4 herds (n=1,122) were randomized to receive either 25mL of 10% butaphosphan and cyanocobalamin or 25mL of sterile water subcutaneously on both days. Each milliliter of Catosal contained 0.05mg of cyanocobalamin and 100mg of butaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 27 publications
6
78
2
3
Order By: Relevance
“…Although several studies had shown the positive effect of butaphosphan in reducing NEB intensity in high-producing dairy cows during the transition period (Furll et al, 2010;Rollin et al, 2010), its mode of action is not clear yet. What is known about the pharmacokinetics of this molecule is that it is rapidly eliminated from the organism after i.v.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although several studies had shown the positive effect of butaphosphan in reducing NEB intensity in high-producing dairy cows during the transition period (Furll et al, 2010;Rollin et al, 2010), its mode of action is not clear yet. What is known about the pharmacokinetics of this molecule is that it is rapidly eliminated from the organism after i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated (Furll et al, 2010;Rollin et al, 2010) that the injection of butaphosphan (2 to 8 g/cow) and cyanocobalamin (1 to 4mg/cow) in dairy cows, can reduce NEB intensity in a dose-dependent fashion with at least three injections of 2 g of butaphosphan and 1 mg of cyanocobalamin. Our results indicate that the use of 1 g of butaphosphan/cow, that is, half of the minimum dose used in other studies, is still able to induce positive effects on NEB and milk production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations